Time-motion analysis of basketball players: a reliability assessment of Video Manual Motion Tracker 1.0 software - Hulka, K.; Cuberek, R.; Svoboda, Z. (Journal of Sports Sciences, 2014)
This study assessed the measurement error of a monitoring system, the Video Manual Motion Tracker 1.0 (VMMT1.0), during time-motion analysis of basketball players. In this study, four reliability parameters were used to assess the measurement error of the system: the systematic bias, the inter-observer reliability, the intra-observer reliability and the absolute reliability. A basketball game video was used for the analysis. To assess the inter-observer reliability, two observers analysed a player`s covered distance for 50 different periods of the game. To assess the relative and absolute reliability of the covered distance, the chosen players were monitored three times by 41 qualified observers. The findings did not indicate a significant systematic bias in the measurement error using the VMMT1.0 (one-way ANOVA, P > 0.05). The intra-observer reliability of the monitoring system was rated as very high (intraclass correlation, ICC = 0.999), similar to its inter-observer reliability (Pearson product-moment correlation, r = 0.994). The absolute reliability does not appear to be significant (standard error of measurement, SEM = 0.34 m). The results showed that the measurement error of the VMMT1.0 is acceptable and comparable with that of other time-motion analysis techniques.